John Adams and the Diplomacy of the American Revolution - Hutson, James H. (Book collections on Project MUSE., 1980)
The figure of John Adams looms large in American foreign relations of the Revolutionary and post-Revolutionary years. James H. Hutson captures this elusive personality of this remarkable figure, highlighting the triumphs and the despairs that Adams experienced as he sought -- at times, he felt, single-handedly -- to establish the new Republic on a solid footing among the nations of the world. Benjamin Franklin, thirty years Adams's senior and already a world-respected figure, was his personal nemesis, seeming always to dog his steps in his diplomatic missions. The diplomacy of the American Revo.